2020
DOI: 10.1002/adem.201901486
|View full text |Cite
|
Sign up to set email alerts
|

High Performance of Low‐Temperature‐Cofired Ceramic with Al2O3/BN Biphasic Ceramics Based on B2O3–Bi2O3–SiO2–ZnO Glass

Abstract: With the rapid development of microelectronic information technology, highpower electronic devices require high heat dissipation. Herein, the preparation of low-temperature cofired ceramic (LTCC) applications with excellent thermal conductivity and dielectric properties is focused. B 2 O 3 -Bi 2 O 3 -SiO 2 -ZnO (BBSZ) glass/Al 2 O 3 /BN green sheets are prepared by tape casting and sintered at 850 C. The crystal phase composition, microstructure, thermal conductivity, thermal expansion coefficient, and dielect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This is an important step as the presence of a redundant coupling agent results in phonon scattering. [ 4 ] The hBN particles thus obtained are further dried for another 12 h at 100°C to finally obtain surface‐modified hBN which can be used for the preparation of the composite body.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important step as the presence of a redundant coupling agent results in phonon scattering. [ 4 ] The hBN particles thus obtained are further dried for another 12 h at 100°C to finally obtain surface‐modified hBN which can be used for the preparation of the composite body.…”
Section: Methodsmentioning
confidence: 99%
“…[1,2] To achieve this, the electronic devices must fulfill certain conditions like high energy density, quick and effective heat dissipation, low dielectric constant, and fast signal transmission. [3,4] Out of this, effective heat dissipation followed by a low dielectric constant is of prime importance. The main heat-generating components in electronic devices are chips, light-emitting diodes, and radio frequency power devices.…”
Section: Introductionmentioning
confidence: 99%
“…The number of closed pores increased as the amount of Al 2 O 3 increased, as illustrated in Figure 4 a,b; when the amount of ZrO 2 was decreased from 40 wt.% to 30 wt.%, the number of closed pores decreased ( Figure 4 e,f). It has already been reported that having a large number of closed pores is harmful to the thermal conductivity of the material and hence the performance of the sintered products [ 32 ]. Closed porosity is seen in the microstructure of the 30Al-O and 40Al-O samples, as shown in Figure 4 a,b.…”
Section: Resultsmentioning
confidence: 99%
“…% BN reduced not only the apparent and open porosity but also the closed pores in the microstructure. It has already been reported that a large number of closed pores is harmful to the thermal conductivity of the material and, hence, the performance of sintered products [ 42 ].…”
Section: Resultsmentioning
confidence: 99%